Application of default treatment in Islamic Banking institution in Malaysia / Nurul Syakirah Sobri. - Sobri, Nurul Syakirah (2019)
Default treatment is one of the operations running in Islamic banking institution. It is closely related to debt culture. In Malaysia, there are specific resolutions and regulations that must be bind by this treatment. This study appoints how default treatment treats defaulters. Hence, this study was using qualitative method by applying internet research and interview session to gain information. E-resources from reliable website were used and a creditable informant was questioned during interview in order to search for accurate data and information. Yet, the pace of this treatment appears to be debated as is it assisting or promoting the same default treatment by any other conventional banking system. This treatment conducted is less emphasis on concept of al-dayn. There is no specific procedure to identify customers’ problems in regard with type of finance they made resulting treatment they received which is believe should be implementing.